Assessment of Neutrophil Chemotaxis Upon G-CSF Treatment of Healthy Stem Cell Donors and in Allogeneic Transplant Recipients - Thunström Salzer, Anna; Niemiec, Maria J.; Hosseinzadeh, Ava; Stylianou, Marios; Åström, Fredrik; Röhm, Marc; Ahlm, Clas; Wahlin, Anders; Ermert, David; Urban, Constantin F. (Frontiers in Immunology, 2018)
Neutrophils are crucial for the human innate immunity and constitute the majority of leukocytes in circulation. Thus, blood neutrophil counts serve as a measure for the im-mune system’s functionality. Hematological patients often have low neutrophil counts due to disease or chemotherapy. To increase neutrophil counts and thereby preventing infections in high-risk patients, recombinant G-CSF is widely used as adjunct therapy to stimulate the maturation of neutrophils. In addition, G-CSF is utilized to recruit stem cells (SCs) into the peripheral blood of SC donors. Still, the actual functionality of neu-trophils resulting from G-CSF treatment remains insufficiently understood. We tested the ex vivo functionality of neutrophils isolated from blood of G-CSF-treated healthy SC donors. We quantified chemotaxis, oxidative burst, and phagocytosis before and after treatment and detected significantly reduced chemotactic activity upon G-CSF treatment. Similarly, in vitro treatment of previously untreated neutrophils with G-CSF led to reduced chemotactic activity. In addition, we revealed that this effect persists in the allogeneic SC recipients up to 4 weeks after neutrophil engraftment. Our data indicates that neutrophil quantity, as a sole measure of immunocompetence in high-risk patients should be considered cautiously as neutrophil functionality might be affected by the primary treatment.